(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2012)
As a result of field researches in 2009, in the area of the Dzoraget River head inflows, the author discovered fields of gold and copper mineralizations of Dzoraget, Snkadzor and Arjidzor. The geological-structural positions of mineralization areas and mineralogical-geochemical features of ore bodies were carried out and their genetic questions have been discussed. Chemical analyses of ore bodies have shown positive results of gold – 0,01–3,1 g/t, silver – 0,1–12,2 g/t, copper – 0,023–2,36% and also platinum and palladium – 0,001–1,2 g/t.